Chronic toxicity, bioavailability and bioaccumulation of Zn, Cu and Pb in Lactuca sativa exposed to waste from an abandoned gold mine - Calabro, María Rosario; Roqueiro, Gonzalo; Tapia Balmaceda, Raúl Esteban; Crespo, Diana Elvira; Bargiela, Martha Fidela; Young, Brian Jonathan (Elsevier, 2023)
Abandoned mines with untreated waste cause environmental pollution. The complex mixture of mining waste includes high metal content, anthropogenic chemicals and sterile rocks. Adverse effects of contaminated soils have been widely assessed by the use of plants. The aim of this study was to assess the chronic toxicity of a contaminated soil by waste from an abandoned gold mine on Lactuca sativa and its relationship with the bioavailability and bioaccumulation of Zn, Cu and Pb. Soil samples were taken from the site of mining waste stacking and a reference site in La Planta (Argentina). Contamination indices were calculated and acute and chronic exposures on L. sativa were carried out. Phytotoxicity indices, morphological and biochemical parameters, and concentrations of Zn, Cu and Pb in pseudo total and bioavailable soil fractions and in plant tissue were determined. Concentration- and time-dependent toxicity effects were observed, especially on plant width, fresh aerial biomass, leaf area and percentage of plants with completely necrotic aerial biomass. High levels of Zn (1453.3 ± 220.3 μg g−1) were found in plant tissue compared to Pb (277.2 ± 18.0 μg g−1) and Cu (255.3 ± 25.6 μg g−1). Toxicological endpoints correlated with metal uptake and mining waste concentration. In addition, bioaccumulation factors correlated with mobilisable and water soluble fractions. The concentration of Pb in aerial biomass surpassed the permissible concentrations in leaf vegetables, even at the reference site, indicating that lettuce crop consumption could be risky for the local population's health. This study demonstrated a strong relationship between metal bioavailability, toxicity endpoints and bioaccumulation, contributing with novel information to future ecotoxicological risk assessments and remediation plans.